The Relationship of Knowledge to the Incidence of Anemia in Pregnant Women - Kanipa, Miranda Marlin; Fionita, Fani; Muh Syahrul (Omni Health Journal, 2025)
Background: Knowledge about anemia during pregnancy is very important for pregnant mothers, because knowledge can affect their attitudes and behaviors in maintaining daily food consumption patterns so that it can prevent anemia during pregnancy. Objective: In this study to determine the relationship between knowledge and the incidence of anemia in pregnant women. Methods: This research used a quantitative analytical design with a cross-sectional study approach. The study was conducted at the Abepura Health Center with a total sample of 38 pregnant women selected through total sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square statistical test with a significance level of 0.05. Results: Based on the results of data analysis, there were 22 respondents (57.9%) who experienced mild category anemia, then 12 respondents (31.6%) who experienced moderate anemia and 4 respondents (10.5%) who experienced severe anemia. Then there were 22 respondents (57.9%) who experienced mild category anemia, then those who experienced moderate anemia as many as 12 respondents (31.6%) and those who experienced severe anemia as many as 4 respondents (10.5%). The results of the statistical test obtained a value of p=0.000 < 0.05, so it can be concluded that the relationship is significant, which means that there is a relationship between knowledge and the incidence of anemia in pregnant women. Conclusion: The conclusion in this study is that there is a relationship between knowledge and the incidence of anemia in pregnant women.